If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7(2n + -5) = (8n + 9) + 7 Reorder the terms: 7(-5 + 2n) = (8n + 9) + 7 (-5 * 7 + 2n * 7) = (8n + 9) + 7 (-35 + 14n) = (8n + 9) + 7 Reorder the terms: -35 + 14n = (9 + 8n) + 7 Remove parenthesis around (9 + 8n) -35 + 14n = 9 + 8n + 7 Reorder the terms: -35 + 14n = 9 + 7 + 8n Combine like terms: 9 + 7 = 16 -35 + 14n = 16 + 8n Solving -35 + 14n = 16 + 8n Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '-8n' to each side of the equation. -35 + 14n + -8n = 16 + 8n + -8n Combine like terms: 14n + -8n = 6n -35 + 6n = 16 + 8n + -8n Combine like terms: 8n + -8n = 0 -35 + 6n = 16 + 0 -35 + 6n = 16 Add '35' to each side of the equation. -35 + 35 + 6n = 16 + 35 Combine like terms: -35 + 35 = 0 0 + 6n = 16 + 35 6n = 16 + 35 Combine like terms: 16 + 35 = 51 6n = 51 Divide each side by '6'. n = 8.5 Simplifying n = 8.5
| 2m=0 | | 2(y+7)=4y+14 | | k^2+4k+2=0 | | 7(2x+4)-9=14x+19 | | 9x+7=9(x+7) | | -5(t-3)+8t=6t-3 | | 4(x)=3x+4 | | 4x+x=90 | | 72+3p=9p | | 3x^2+24=27 | | 3x-9=3(x-1) | | 8x-60=4x | | 12x+4=64 | | 0.12(y-9)+0.08y=0.16y-0.07(20) | | 52x=13 | | 5t^2-13t-6= | | -(2z+2)+3(2z+6)-2z= | | 0.80x+0.20(110)=0.40(75) | | 4x+x=8x-60+x | | 4x^2+16x+16=1 | | -27-7x=-9-4x | | 4x+18=5x-12 | | -49-4x=5-10x | | -6(x-3)+6=24 | | 120-3x=24x+18 | | 5y-8=9y | | 3(12-8)=x | | 3(12-8)=8 | | 12x+24=4x-48 | | 3(x-8)=x | | -4[7+4(-9+4)]+12=x | | -2(3x-3)=3x |